Economic globalisation and Africa's quest for greener and more inclusive growth: The missing link - Isaac Kwesi Ofori; Andreas Freytag; Simplice Asongu (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2023)
This study examines the contingency and threshold effects of economic freedom in the economic globalisation (EG) and inclusive green growth (IGG) relationship in Africa. Based on macro data for 22 African countries and the Driscoll-Kraay standard errors with fixed effects instrumental variable regression, the following findings are established. First, Africa's mostly unfree economic setting, conditions EG to reduce IGG. Second, when we disaggregate EG into its financial and trade globalisation components, we find that the IGG-impeding net effect of the latter is rather striking. Third evidence from our threshold analysis suggests that by improving Africa's mostly unfree economic architecture to 60% (moderately free) or 80% (free), the IGG-deteriorating net effects of EG are mitigated (but not nullified). We conclude that unless effort is made to improve Africa's economic architecture level, the envisaged IGG gains of economic globalisation might prove elusive.
Keywords: F14; F4; O56; Q01; 330; Africa; Economic freedom; Economic globalisation; Inclusive green growth